Silencing of PTGS2 exerts promoting effects on angiogenesis endothelial progenitor cells in mice with ischemic stroke via repression of the NF‐κB signaling pathway. Issue 12 (21st June 2019) - Zhou, Zheyi; Lu, Changjun; Meng, Shuhui; Dun, Linglu; Yin, Nannan; An, Hongwei; Xu, Hong; Liu, Guocheng; Cai, Yefeng
Abstract: The objective of the current study is to investigate the effect of PTGS2 on proliferation, migration, angiogenesis and apoptosis of endothelial progenitor cells (EPCs) in mice with ischemic stroke through the NF‐κB signaling pathway. Middle cerebral artery occlusion (MCAO) model was established in mice. EPCs were identified, in which ectopic expression and depletion experiments were conducted. The mRNA and protein expression of related factors in tissues and cells were measured. Besides, proliferation, migration, angiogenesis, and apoptosis, as well as cell cycle distribution, of cells were determined. MCAO mice showed overexpression of interleukin‐6 (IL‐6), IL‐17, and IL‐23, and increased positive protein expression of PTGS2, as well as expression of PTGS2, nuclear factor‐κB (NF‐κB), tumor suppressor region 1 (TSP‐1) and Bcl‐2‐associated X protein (Bax), but underexpression of vascular endothelial growth factor (VEGF), S‐phase kinase associated protein 2 (Skp2), and B‐cell lymphoma 2 (Bcl‐2). Moreover, ectopic expression of tumor necrosis factor‐α significantly elevated the expression of PTGS2, NF‐κB, TSP‐1, and Bax, as well as cell apoptosis and cell cycle arrest, but decreased the expression of VEGF, Skp2, and Bcl‐2, as well as proliferation, migration and angiogenesis of EPCs, and the PTGS2‐siRNA group showed an opposite trend. Taken together, we conclude that the specific knockdown of PTGS2 expression could repress the NF‐κB signaling pathway, thereby inhibits apoptosis and promotes proliferation, migration and angiogenesis of EPCs, providing protective effect on mice with ischemic stroke. Abstract : Taken together, we conclude that the specific knockdown of PTGS2 expression could repress the NF‐κB signaling pathway, thereby inhibits apoptosis and promotes proliferation, migration and angiogenesis of endothelial progenitor cells (EPCs), providing protective effect on mice with ischemic stroke.